(untitled) (American Journal of Islam and Society, 1999)
The article identifies the global growth of the war industry and weapons trade along with inequitable distribution of wealth and unjust economic systems as major reasons for the tack of peace and prosperity everywhere in the world. The article discusses the political economy of war and its implications on the socioeconomic elements of society. The paper illustrates through an economic evaluation of the Gulf War and the Iran-Iraq War the enormous damage that modem weapons and modem wars can burden a nation and its civilian population. The article does not offer any specific strategies to deal with either the ravages of the war industry during war as well as during peace, or with the inherent inequity in the economic system. But the author hopes that the awareness of these problems and their incredibly devastating consequences will exhort everyone into address them.